PENGATURAN PENGELOLAAN BARANG MILIK DAERAH DAN HUBUNGANNYA DENGAN PENGURUSAN KENDARAAN DINAS DI KOTA KUPANG - Lahal, Josvia Ekomardih; Stefanus, Kotan Y; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
The issue of permits for the use of official vehicles is an administrative legal device used by the government to control Civil Servant officials who use official vehicles. The use of official vehicles outside the implementation of official duties can be found clearly during holidays, especially major holidays, even Sundays are often found. in shopping centers, as is often found in Kupang City, but is considered normal without any supervision from the Regional Government. Based on the author's observations, the background of the main problem can be formulated: How are the management of regional property in Kupang City and how are official vehicles managed in Kupang City.To answer this problem, this research was carried out using empirical legal research and the Qualitative Descriptive Analysis Method in accordance with the data obtained while still paying attention to theory, principles and legal rules, so this research is research that originates from primary, secondary and tertiary data using a juridical approach. Empirical Normative. The results of this research show that operational service vehicles are only used for official purposes that support basic tasks and functions, operational service vehicles are limited to use on office work days and operational service vehicles are only used within the city, and use outside the city is excluded with written permission from the head of a government agency or official. assigned according to competency and the provision of official vehicles to officials who receive these official vehicles, namely ASN who have positions from echelon 4, echelon 3 and echelon 2, are given according to their needs and usage when carrying out their work within the scope of Kupang City and there must also be supervision from BPKAD means that the planning expected by management can be fulfilled and run well, because ASNs who like to use official vehicles outside of office hours can be seen from fuel coupons that expire before the specified date and vehicle parts that are damaged before the time, which means there is use. excess of the ASN. The conclusion is the management of regional property in Kupang City, namely: The rules set by the Regional Government of Kupang City regarding the use of official vehicles are clear and there are administrative sanctions, but there are still ASN who still use official vehicles outside office hours.The suggestion is: In its supervision, BPKAD must look regardless of position in following up on violations committed by ASN when using official vehicles outside working hours.